Studying Solutions to Enhance the Quality of Casting Pressure Products by Ultrasonic Testing - Huynh , Nguyễn Hoàng; Mai , Thị Thu Huyền. (Journal of Technical Education Science, 2012)
The application range of pressure die casting technology has increasingly been enlarged worlwide as well as in Vietnam. Pressure die casting products have been used in many fields such as manufacturing machine parts for motorcycle, car, diesel engine, medicine, education, civil aviation, etc. Testing and analysing technologies are important to improve the products’ quality after casting. This article reports an ultrasonic testing technique in examining defects of die casting industry